THE TEN CRITICAL SUCCESS FACTORS IN SOFTWARE DEVELOPMENT PROJECTS - Indrajit, Richardus Eko (Informatika, Universitas Jenderal Soedirman, 2024)
In the rapidly evolving landscape of technology, software development plays a critical role in driving innovation and enhancing organizational efficiency. This paper explores the Critical Success Factors (CSFs) that significantly influence the outcomes of software development projects. By examining key components such as stakeholder involvement, effective commu- nication, and robust project management practices, the paper provides a comprehensive framework that can guide teams toward achieving their project goals. The analysis highlights the importance of well-defined requirements, skilled teams, and strong project management, while also addressing challenges unique to global software development. The findings suggest that a multifaceted approach, which integrates technical proficiency with effective communication and stakeholder engagement, is essential for navigating the complexities of software development and ensuring project success.